Neuropsychological models of autism spectrum disorders - behavioral evidence and functional imaging - Dziobek, I.; Bölte, Sven (2011)
Objective: To review neuropsychological models of theory of mind (ToM), executive functions (EF), and central coherence (CC) as framework for cognitive abnormalities in autism spectrum disorders (ASD). Methods: Behavioral and functional imaging studies are described that assess social-cognitive, emotional, and executive functions as well as locally oriented perception in ASD. Results: Impairments in ToM and EF as well as alterations in CC are frequently replicated phenomena in ASD. Especially problems concerning social perception and ToM have high explanatory value for clinical symptomatology. Brain activation patterns differ between individuals with and without ASD for ToM, EF, und CC functions. An approach focussing on reduced cortical connectivity seems to be increasingly favored over explanations focussing on single affected brain sites. Conclusions: A better understanding of the complexities of ASD in future research demands the integration of clinical, neuropsychological, functional imaging, and molecular genetics evidence. Weaknesses in ToM and EF as well as strengths in detail-focussed perception should be used for individual intervention planning.